Innovación y eficiencia: Estudio empírico de las regiones europeas 2000–2010 - Verástegui Huanca, Lucio Leo (2018)
Objective: The main objective of this research work is to carry out an empirical research on the efficiency of innovation in European regions, through Data Envelopment Analysis. Method: To achieve this objective, information was used from 191 regions belonging to 27 countries of the European Union consolidated in the database IAIF - RIS (EU). Results: Efficiency scores related to innovation in the regions studied are shown. Conclusions: It will be useful for future analyzes related to efficiency, productivity and potential improvement of innovation systems.